A remarkable case report of an interrupted inferior vena cava with hemiazygos and transhepatic continuation - Masino, Federica; Muscatella, Gianmichele; Montatore, Manuela; Gifuni, Rossella; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Inferior vena cava (IVC) interruption with azygos/hemiazygos continuation is an extremely uncommon congenital vascular anomaly, which may present with multiple variants. As a result, it is challenging to find in the literature the same anatomical variant.We report a unique case of an interrupted IVC with hemiazygos and transhepatic continuation in an 83-year-old female patient. The case was evaluated by performing Computed Tomography (CT) as imaging modality, with a multiphase protocol, able to detect accurately this complex vascular anomaly.The purpose of this case report is not only to present this remarkable case but also to briefly show the types of interrupted IVC, starting from the anatomy and the embryology of the IVC and the azygos system, and to discuss the value of imaging in detecting the vascular anomaly.